2012
DOI: 10.19030/tlc.v9i4.7302
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of High Scientific Literacy, Self-Efficacy, And Achievement Motivation On Teachers Ability To Compose Effective Tests: Case Study From Manado, Indonesia

Abstract: This research was conducted to determine the effects of high scientific literacy, self-efficacy, and achievement motivation on teachers ability to compose effective tests. It was conducted among junior high school science teachers in Manado, North Sulawesi Province, Indonesia, from April to September 2011, using a cross-sectional survey design. The instruments used in this research consist of questions to measure scientific literacy and teachers ability to make tests, and questionnaires to investigate the self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Also, these research results show similarity with the study of Akgün et al (2014), in which they found that the level of science and technology literacy affects self-efficacy beliefs and attitude levels positively. In his study, Poluakan (2012) stated that teachers' science literacy levels strongly affect their success motivation. In another study examining the relationship between science literacy and self-efficacy of physics teachers, it is stated that there is a strong and positively significant relationship between science literacy and science teaching self-efficacy (Latifah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Also, these research results show similarity with the study of Akgün et al (2014), in which they found that the level of science and technology literacy affects self-efficacy beliefs and attitude levels positively. In his study, Poluakan (2012) stated that teachers' science literacy levels strongly affect their success motivation. In another study examining the relationship between science literacy and self-efficacy of physics teachers, it is stated that there is a strong and positively significant relationship between science literacy and science teaching self-efficacy (Latifah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%